Gender Equality as Human Rights: Efforts to Empower Women and Improve Family Welfare in Boja Village - Anis Widyawati; Dian Latifiani; Lyna Latifah; Rohadhatul Aisy; Shofriya Qonitatin Abidah; Siti Amatil Ulfiyah; Amel Ellsamia Indiyani; Adilia Putri Kusuma; Heru Setyanto (The Digest: Journal of Jurisprudence and Legisprudence, 2024)
The research aims to explore the socio-political dimensions of gender justice and human rights, emphasizing women's political equality while ensuring appropriate support for family life. Using a combination of field research (non-doctrinal) and a literature review of primary sources, including those related to Boja Village, the paper analyzes legislative changes and economic initiatives that have enhanced women's status and family welfare. The study also examines global and national gender-equality indices, evaluating their progress through both quantitative indicators and qualitative policy assessments/public opinion. The discussion highlights the complex roles of governments, non-governmental organizations, and women’s activist groups in advocating for gender parity on a global scale. While many aspects of life have seen improvements, cultural and economic challenges, along with institutional remnants, continue to hinder equal opportunities for both men and women. The coordinated approach to women’s and family welfare emphasizes gender- and culture-sensitive empowerment of the individual. The chapter concludes with policy and practice recommendations aimed at fostering more gender-sensitive interventions, accelerating progress toward universal human rights, and advancing the sustainable development agenda.